Analysis of Factors Affecting Druging Compliance in Lung Tuberculosis Patients: Theory of Health Belief Model (HBM) in the Working Area of the Health Center, Dompu City - Supriano, Andiri; Katmini, Katmini (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Tuberculosis is an infectious disease caused by TB bacteria called Mycobacterium tuberculosis, which mostly attacks the lungs (80%), but can also attack other organs such as bones, lymph glands, joints, lining of the brain, intestines, kidneys. , genitals, and others. The purpose of this study in general was to determine the effect of the Health Belief Model theory on medication adherence to tuberculosis patients. This research is a quantitative study with the method of observation and cross sectional approach. The research sample was 119 tuberculosis sufferers. The independent variables are perceived vulnerability, severity, barriers, cues for action, perceived benefits and self-efficacy. Adherence to taking medication in tuberculosis patients as the dependent variable. The results showed that simultaneously there was an effect of variable X on Y with a significance value of 0.000 and a large effect of 10.2%. And simultaneously it shows that there is an influence of variables X and Y with a significance value of 0.000 and a large influence of 12.8%. Data analysis using path analysis. Simultaneously there is an effect of the application of the Health Belief Model theory on adherence to taking medication in tuberculosis patients.